Cryptocurrency investment: Evidence of financial literacy, experience, and risk tolerance - Chalimatuz Sa’diyah; Bambang Widagdo; Fika Fitriasari (Investment Management & Financial Innovations)
The growing popularity of cryptocurrency as an investment choice among millennials demonstrates their inclination toward digital advancements and openness to exploring diverse investment opportunities. The study examines how financial literacy factors impact experience regret, investment decisions, and risk tolerance, while financial literacy also affects investment decisions, with experience regret and risk tolerance acting as a mediator. The study comprises 295 participants from the millennial demographic in Indonesia who are engaged in cryptocurrency investment. The data collection techniques employed in this study involve non-probability sampling methods through the distribution of questionnaires. The analysis in this study employs Structural Equation Modeling (SEM) in conjunction with Partial Least Squares (PLS) analysis tools. The results of this study suggest that financial literacy positively impacts regret experience, investment decisions, and risk tolerance with the respective sample values of 0.146, 0.397 and 0.449. Additionally, regret experience negatively influences investment decisions with a sample value of –0.385, while risk tolerance positively influences investment decisions with a sample value of 0.198. Financial literacy has a negative impact on investment decisions when regret experience acts as a mediator with a sample value of –0.056, but a positive impact when risk tolerance serves as a mediator with a sample value of 0.089. This complex relationship highlights the importance of considering multiple factors, including financial literacy, regret experience, and risk tolerance, in understanding and predicting investment decisions among individuals, particularly in the context of the millennial generation investing in cryptocurrency in Indonesia.